Colour perception in pseudophakia. Issue 10 (October 1982) - Jay, J L; Gautam, V B; Allan, D
Abstract : Minor differences in colour perception between pseudophakic, phakic, and spectacle aphakic eyes were identified by the Pickford-Nicholson anomaloscope and the Farnsworth-Munsell 100-hue test. The results suggest that pseudophakic eyes are more sensitive to red and less sensitive to blue than aphakic eyes corrected with spectacles. Spectrophotometer measurements reveal that the Rayner-Pearce posterior chamber intraocular lens used in this study transmits an evenly balanced colour spectrum, whereas an aphakic spectacle lens exhibits significant colour distortion, reducing the red and enhancing the blue transmission. This distortion may possibly be attributed to the increased chromatic aberration in the spectacle lens compared with the intraocular lens.